TaqMan Real-Time Quantification of Epstein-Barr Virus in Severe Early Childhood Caries - Yildirim, Sibel; Yildiz, Esma; Kubar, Ayhan (European Journal of Dentistry, 2010)
Objectives: Early childhood caries (ECC) has several risk factors and it is important stressful/ painful events of childhood and immunosuppression may occur during this unique rampant caries pattern. The changes in the host immune competence by compromised cellular immune system functions can activate Epstein Barr virus (EBV). The objective of this study was to determine whether the supragingival plaque samples of severe-ECC (S-ECC) patients harbor more EBV load than the non-carious healthy children by quantitative TaqMan Real-Time polymerase chain reaction (PCR).Methods: Sixty subjects, including 30 S-ECC patients as well as age and gender matched 30 caries- free patients were studied. The supragingival plaque samples were collected from patients by brushing their teeth for 1 minute and the toothbrush was washed in 1 ml of sterile deionized water. After viral DNA extraction, TaqMan real-time PCR assay was used to quantify EBV DNA. Dental treatments were completed for all S-ECC patients and they were called for routine controls. Only 10 treated S-ECC patients were come to the 3rd months control and post-treatment viral sampling was made in the same manner.Results: EBV DNA was detected 16 of 30 S-ECC patients and 6 of the healthy controls (P<.001). There was no relationship between baseline and post-treatment samples of 10 treated S-ECC patients.Conclusions: The results of the study suggest that oro-dental hygiene motives of S-ECC patients might be important contributory factor for S-ECC and EBV would not be involved in the etiopathogenesis of ECC. (Eur J Dent 2010;4:28-33)
Keywords: Early childhood caries; Epstein-Barr virus; TaqMan Real-Time PCR